Variscan overthrusting, fluid flow and the genesis of magnetite ore-bodies at Azenhas area (Pedrógão, Ossa-Morena Zone, SE Portugal) - A., Mateus (2005)
In the Azenhas area (SE Portugal), an important segment of a regional WNW-ESE Variscan thrust can be observed. The hanging wall felsic metavolcanics carried from ENE are evolved rhyolite tuffs. The underlying sequence is mainly composed of variably metasomatised allochthonous amphibolites that are believed to represent an ophiolite slice tectonically overlying the autochthonous Moura-Ficalho Complex. Within this latter sequence, numerous WNW-ESE thrusts with prevailing displacement towards W-SW cut prior sub-parallel structures with northwards thrust shear. According to the observed crosscutting relationships and to the available petrographic data, the metasomatism experienced by the lower amphibolite sequence took place mainly before the emplacement of the upper slices of amphibolites, preceding therefore the installation of the felsic metatuffs. Magnetite ore-bodies are found within strongly metasomatised amphibolites immediately below the major WNW-ESE thrust zone or its subsidiary thrust structures. Their genesis is envisaged as a result of a complex chemical reaction path that involves the ascent of aqueous oxidising fluids under a reverse temperature gradient generated during the tectonic emplacement of amphibolites. In order to test the geological plausibility of the thermal evolution and the time span needed for ore genesis a one-dimensional numerical model was developed. This model enables the tracing of vertical thermal profiles at different times and accounts for the thrust emplacement history, incorporating variable erosion rates of the rock sequence. The results obtained show that an inverted thermal gradient in the thrusted sequence is kept for over 1 Ma and a regular temperature increase (from 400ºC to 500ºC) is observed in the underlying rocks lasting for 4.5 to 5.5 Ma.